In-Silico Screening of Phytochemicals for Identification of Alternative Therapy for Thyroid Cancer - Swapnesh Bhaduri (International Journal of Toxins and Toxics, 2025)
Thyroid cancer remains a significant health concern globally, necessitating the exploration of novel therapeutic alternatives to improve treatment outcomes. This study targets COT kinase (Cancer Osaka Thyroid Kinase), a protein implicated in the progression of thyroid cancer, using molecular docking methods with various phytochemicals to identify potential therapeutic compounds. PyRx and Discovery Studio were employed to evaluate the interactions and binding affinities of a diverse set of natural compounds with the target protein. A comprehensive selection of 150 alkaloids, 150 terpenoids, and 149 flavonoids were screened to assess their potential efficacy in modulating COT kinase activity. Through silico analysis, the study aims to identify phytochemicals that exhibit strong binding affinities with COT kinase and could potentially serve as lead compounds for the development of new therapeutic agents. By exploring a wide variety of natural compounds, the research seeks to broaden the scope of potential treatment options for thyroid cancer, particularly for cases where existing therapies may be less effective or associated with significant side effects. The findings from this study will contribute valuable insights into the molecular interactions between phytochemicals and COT kinase, offering a foundation for future research and development in the field of thyroid cancer treatment. By identifying compounds with promising therapeutic potential, this research may pave the way for the development of more targeted and effective treatments for thyroid cancer, ultimately improving patient outcomes and quality of life.
Keywords: COT kinase; Docking; Phytochemicals; in-silico; thyroid cancer